Converter for content-to-head style syntactic dependencies - Rehbein, Ines; Steen, Julius; Do, Bich-Ngoc; Frank, Anette (Universität, 2020)
A set of Python scripts that convert function-head style encodings in dependency treebanks in a content-head style encoding (as used in the UD tree...
Production date: 2017
Kind of data: Python scripts
Gesehen am 15.04.2020
Keywords: Forschungsdaten; Datenbank